Two Cases of Eosinophilic Variant Chromophobe Renal Cell Carcinoma, with a Rare Association of Right Atrial Myxoma in One of them - Yeshvanth, Sunil Kumar; Permi, Harish S; Laxminarayana, Kishan Prasad Hosapatna; Shrinivas, Teerthanath; Shetty, Jayaprakash K (Journal of Laboratory Physicians, 2011)
Chromophobe renal cell carcinoma is a relatively uncommon variant of renal cell carcinoma. Eosinophilic variant of chromophobe renal cell carcinoma (EVCRCC) is still less frequent and is composed predominantly of small to medium-sized cells with abundant granular eosinophilic cytoplasm. We report two cases of EVCRCC, with one having a rare association of right atrial myxoma. We present these cases, due to the rarity of EVCRCC and an unusual association of right atrial myxoma in one of them. Both patients recovered well after surgery, with no recurrence or metastasis after 2 years of follow-up.
Keywords: Atrial myxoma; chromophobe renal cell carcinoma; eosinophilic variant